IMPLEMENTASI BAI` AL-INAH DAN KAFALAH-IJARAH DALAM SYARIAH CHARGE CARD - Yusuf Prasetiawan, Ahmad; Erlina, Fatni (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to find out how the implementation of the bai` al-inah contract with kafalah-ijarah in the issuance of Islamic credit cards. These two types of contracts are used in two different countries, namely Malaysia and Indonesia, with very different performance achievements in Islamic banking in the two countries. The method used in this study is comparative analysis. Source of data is literature literature. The discussion is carried out with a legal and benefits approach. The results show that the bai` al-inah contract, materially, receives a lot of rejection, although not in absolute terms. But there are loopholes other than a few Ulama who allow it, namely the type of bai` al-wafa` with the involvement of a third party. However, the contract between the two in sharia credit card transactions is not the only factor. Islamic financial performance is more determined by customer behavior.